Synthesis Of Zinc Oxide Nanoparticles Using Gallic Acid Characterization And Evaluation Of Antioxidant Activity - Kabeer, Saiful Munir Sultan Syed Ahmad (Universiti Sains Malaysia, 2022)
Zinc oxide (ZnO) nanoparticles are widely used in biomedical industries due to their antioxidant, anti-cancer, anti-inflammatory, antibacterial and antifungal properties. The synthesis of ZnO nanoparticles via the green synthesis pathway has become the focus of the researcher over the past years due to its being environmentally benign, less harmful and non-toxic. In this present study, the synthesis of ZnO nanoparticles via a chemically green synthesis pathway using the chemical precipitation technique was done. A precursor of zinc acetate dihydrate and gallic acid as a reducing and capping agent was used. The effect of varying the pH of solutions from 7 to 11 was studied to synthesize ZnO nanoparticles. Besides, the molar ratios of gallic acid to zinc acetate dihydrate were also studied by changing from 1.0% to 4.0% during the synthesis process. The synthesized ZnO nanoparticles were characterized under different techniques, including Ultraviolet-visible (UV-Vis) spectroscopy, Fourier-transform infrared spectroscopy (FT-IR), Energy-dispersive X-ray spectroscopy (EDX) and Scanning electron microscope (SEM). The morphology and particle size were observed using SEM under both synthesis conditions. The particle sizes were estimated at 269.65 ± 8.23 nm, 234.91 ± 7.51 nm and 118.76 ± 1.27 nm for pH 9, 10 and 11, respectively. The results illustrated that the synthesis under pH 7 and 8 led to agglomeration. Moreover, the particle sizes were estimated at 118.76 ± 1.27 nm, 201.85 ± 16.06 nm, 198.49 ± 15.25 nm, 174.86 ± 6.93 nm, and 99.70 ± 2.78 nm for various molar ratio gallic acid to zinc precursor 1.0, 1.5 3.0, 3.5 and 4.0%, respectively. The results also revealed that varying molar ratios had influenced the different types of shapes of ZnO nanoparticles. Finally, the optimum from both synthesis conditions (pH 11 and GA: Zn of 4.0%) was used to study antioxidant activity. The ZnO nanoparticles exhibited good antioxidant activity, with IC50 values of 28.88 μg/ml and 25.40 μg/ml for DPPH and ABTS, respectively. This suggested that ZnO nanoparticles could have potential uses in biomedical fields and act as an abiotic elicitor to enhance the biosynthesis of secondary metabolites in "in vitro" plant cell cultures.